Prevalence, antimicrobial resistance and biofilm forming ability of Escherichia coli in milk, animal handlers and slurry samples from dairy herds of Punjab, India - Vijay, Deepthi; Bedi, Jasbir Singh; Dhaka, Pankaj; Singh, Randhir; Singh, Jaswinder; Arora, Anil Kumar; Gill, Jatinder Paul Singh (Frontiers in Veterinary Science, 2025)
Antimicrobial-resistant Escherichia coli serves as an indicator for monitoring the occurrence of antimicrobial resistance (AMR) at the human, animal, and environmental interface. The present study employs a ‘One Health’ framework to determine the prevalence, phenotypic and genotypic characterisation of the AMR profile and biofilm forming ability of E. coli isolates from milk, hand swabs and slurry samples of 405 dairy herds in Punjab, India. An overall prevalence of E. coli was 34.3% (139/405) (95% CI: 0.30 to 0.39) from pooled milk samples, 9.1% (37/405) (95% CI: 0.06 to 0.12) from the hand swabs of animal handlers and 64.4% (261/405) (95% CI: 0.60 to 0.69) in the slurry samples. Multidrug resistance (resistance to 3 or more classes of antimicrobials) was exhibited by 24.4% (34/139) of E. coli isolates from milk, 40.5% (15/37) from hand swabs, 60.5% (158/261) from slurry samples. Moreover, of the E. coli isolates, 11.51% (16/139) from milk, 24.32% (09/37) from hand swabs and 31.42% (82/261) from slurry samples were resistant to 5 or more antimicrobial classes. On molecular characterisation, 19.4% (27/139) of E. coli isolates from milk, 37.8% (14/37) from hand swabs, and 33.3% (87/261) from slurry samples harboured various genes. Principal component analysis and Shannon-Wiener diversity indices highlighted varying β-lactamase (ESBL/AmpC β-lactamase) gene distributions across samples, with milk exhibiting the highest diversity. Logistic regression analysis revealed a significant protective effect of milk hygiene scores against E. coli occurrence (OR = 0.18; 95% CI: 0.13–0.26, p < 0.001), while linear regression demonstrated a significant negative association between milk hygiene scores and the Multiple Antibiotic Resistance (MAR) index (p = 0.02). Biofilm assays revealed that 19.2% of isolates were strong biofilm formers, with a strong association (p < 0.01) between biofilm formation potential and MAR index. The multidrug-resistant (MDR) isolates were predominantly moderate biofilm producers, with 23.5% (milk), 20% (hand swabs), and 24.1% (slurry) classified as strong biofilm formers. The study findings underscore the need for One Health-integrated strategies to holistically address AMR challenges at the dairy-environment interface.